Klotho overexpression protects human cortical neurons from β-amyloid induced neuronal toxicity - Mohammed R. Shaker; Salam Salloum-Asfar; Rowaida Z. Taha; Ibrahim Javed; Ernst J. Wolvetang (Molecular Brain)
Abstract Klotho, a well-known aging suppressor protein, has been implicated in neuroprotection and the regulation of neuronal senescence. While previous studies have demonstrated its anti-aging properties in human brain organoids, its potential to mitigate neurodegenerative processes triggered by β-amyloid remains underexplored. In this study, we utilised human induced pluripotent stem cells (iPSCs) engineered with a doxycycline-inducible system to overexpress KLOTHO and generated 2D cortical neuron cultures from these cells. These neurons were next exposed to pre-aggregated β-amyloid 1–42 oligomers to model the neurotoxicity associated with Alzheimer’s disease. Our data reveal that upregulation of KLOTHO significantly reduced β-amyloid-induced neuronal degeneration and apoptosis, as evidenced by decreased cleaved caspase-3 expression and preservation of axonal integrity. Additionally, KLOTHO overexpression prevented the loss of dendritic branching and mitigated reductions in axonal diameter, hallmark features of neurodegenerative pathology. These results highlight Klotho’s protective role against β-amyloid-induced neurotoxicity in human cortical neurons and suggest that its age-related decline may contribute to neurodegenerative diseases such as Alzheimer’s disease. Our findings underscore the therapeutic potential of Klotho-based interventions in mitigating age-associated neurodegenerative processes.